Association of latrine and waste disposal conditions with water and kitchenware contamination in peri-urban Lusaka - Min-Li Chua; Imasiku Nyambe; Shigeo Fujii; Taro Yamauchi; Hidenori Harada (npj Clean Water, 2022)
Abstract Sanitation facility conditions and waste disposal practices are hypothesized to affect the fecal contamination of drinking water and kitchenware. The present study aimed to examine the physical conditions of sanitation facilities and waste disposal locations as well as determine the concentrations of Escherichia coli in drinking water, cups, dishes, flies, toilet floors, and kitchen floors. A total of 336 samples were collected from 17 households in peri-urban Lusaka. Generalized linear mixed models showed that six out of seven physical pit-latrine conditions, waste disposal practices, and kitchen hygiene practices had significant effects on the contamination of either kitchenware or drinking water. The results highlighted that improving the physical pit-latrine conditions, dumpsite location, washing water, and kitchenware-drying location may potentially reduce fecal contamination of drinking water, cups, and dishes.